THE EFFECTIVENESS OF THE KUMON METHOD WITH TAPERTIS MEDIA TOWARDS UNDERSTANDING THE MULTIPLICATION CONCEPT OF ELEMENTARY SCHOOL STUDENTS - Sunarsih Sunarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2022)
This study aims to determine the effectiveness of the Kumon method with tapertical media on understanding the concept of multiplication in mathematics. The use of tapertis media aims to make learning more interesting and students easily accept lessons in school. This research uses a quantitative approach to the type of experimental research. This research was conducted at Lanjan 01 Public Elementary School, Sumowono District, Semarang Regency, Central Java. The population in this study were all students in SDN Lanjan 01. The sample was students in grade IV SDN Lanjan 01. The results showed that: There were differences in the average pretest scores the experimental class is higher than the control class (51.91> 48.17). There is a difference in the average posttest value of the experimental class which is also higher than the control class (80.64> 75.52). In addition, the results of the experimental class n-gain test were greater than the control class (0.507> 0.425). T test results also showed that the average experimental class was higher than the control class (80.64> 72.52). The t test results also showed a significance level <0.05, i.e. 0.000 <0.05 and 0.001 <0.05. Then it can be concluded that the kumon method with tapertis media is effective in increasing understanding of elementary students' multiplication concepts